Formation and Development of Taproots in Deciduous Tree Species - Kościelniak, Paulina; Glazińska, Paulina; Kȩsy, Jacek; Zadworny, Marcin (Frontiers in Plant Science, 2021)
Trees are generally long-lived and are therefore exposed to numerous episodes of adverse environmental conditions. Some trees have evolved long taproots as an adaptive response to drought, increasing their ability to acquire water from deeper soil layers. Despite their significant roles, little is known about the genes, phytohormones, micro-RNAs regulating taproot formation and growth, or the effect of external factors such as drought. The interaction of internal and external stimuli, involving complex signaling pathways, regulates taproot growth through the integration of taproot tip formation and the regulation of cell division in the root apical meristem (RAM), as well as subsequent elongation. Assuming that the RAM is the primary regulatory center responsible for taproot growth and cessation, knowledge of the factors affecting the RAM function would provide fundamental information on the mechanisms affecting taproot development.